Students’ Perception on Utilization of Technology in Listening Learning - Putu Wahyu Sudewi; Adi Isma (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
The learning process in listening practice is only limited to one type of text. Students have difficulty adapting to various types of audio material. Learning focuses more on speaking and writing skills than listening. As a result, students are less trained in active listening. A deep understanding of these issues helps to develop more effective learning strategies and supports students in overcoming these obstacles. Technological developments in education have influenced students' learning styles. This research aims to describe how students perceive the utilization of technology, specifically podcasts, to enhance their listening skills. The research employed a qualitative research method, specifically a case study, to gather data through questionnaires and interviews. The participants were EFL learners focusing on Listening for Professional Purposes, with 40 students completing the questionnaires and 10 representative students being interviewed. Findings reveal that students had a favorable response to utilizing podcasts as a means of enhancing their listening skills. They appreciated the simplicity, flexibility, engagement, and enjoyment of employing podcasts as media of learning. Findings from this research help lecturer develop curriculum and learning materials that better suit with students’ preferences and needs. This research allowed for the creation of more interesting and technology-relevant materials that are more acceptable to students.